Las mujeres cacaocultoras gestoras del desarrollo sostenible en el postconflicto colombiano: municipio Maripí (2019)
This study is part of the project called "Familiar cocoa agriculture and associativity in the West of Boyacá" managed by the GIDICON Group of the Pedagogical and Technological University of Colombia. The research developed tries to highlight the transcendental role that the cocoa-grower woman has played in the sustainable regional development of the Municipality of Mari pi Boyacá in the post-conflict period. To this end, from the case study, in the association ASOCAPAZ, it is evident how the woman with her enterprising spirit is the protagonist of sustainable development: (i) in the social sphere, generating actions from the rural family, in the search of the countryside rebirth as an opportunity for inclusion; (ii) in the economic sphere, its leadership supports the activities necessary to overcome poverty; and (iii) in the environmental perspective, their actions contribute to the application of Good Environmental Practices and Good Agricultural Practices, in this sense, the substitution of crops allows an important improvement in the environment of the Municipality of Maripi.